1992
DOI: 10.1021/es00031a014
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth distributions in catalysts and airborne particles

Abstract: Zeolite cracking catalysts used by petroleum refineries were analyzed for 38 elements. Concentration patterns of rare earth elements (REEs) in 10 zeolite catalysts show an enhancement of light REEs relative to the crustal abundance pattern, resembling those measured in refineries emissions. Release of zeolite catalyst material from fluidized catalytic crackers and incorporation of zeolite catalysts into refined oil provide new atmospheric elemental signatures for tracing emissions from refineries and oil-fired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 11 publications
4
49
0
Order By: Relevance
“…In the past, trace metal assessments of urban soils frequently examined trace metals that were traditionally significant for the environment and health, particularly Cd, Cu, Pb, and where leaded gasoline is no longer in use (Kitto et al, 1992;Huang et al, 1994;Zayed et al, 1999a&b;Sutherland, 2003;Zereini et al, 2004). These elements have been chosen for their usefulness in the identification of sources of contaminants and their potential health implications.…”
Section: Inclusion Of Other Trace Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, trace metal assessments of urban soils frequently examined trace metals that were traditionally significant for the environment and health, particularly Cd, Cu, Pb, and where leaded gasoline is no longer in use (Kitto et al, 1992;Huang et al, 1994;Zayed et al, 1999a&b;Sutherland, 2003;Zereini et al, 2004). These elements have been chosen for their usefulness in the identification of sources of contaminants and their potential health implications.…”
Section: Inclusion Of Other Trace Metalsmentioning
confidence: 99%
“…It has been documented that atmospheric emissions of REEs and PGEs can be attributed to abrasion and corrosion of catalytic converters coupled with fuel combustion, as fossil fuels contain trace quantities of REEs (0.5 -2.0 % in the oxide forms), and catalytic converters in vehicles are now dominantly made with PGEs (Kitto et al, 1992;Huang et al, 1994;Zereini et al, 2004). Work conducted in U.K. towns over the period 1982-1998 has clearly demonstrated that there has been an increase in PGEs in road dust Hutchinson et al, 2000).…”
Section: Inclusion Of Other Trace Metalsmentioning
confidence: 99%
“…The cracking catalyst contains high concentrations of La and Gd. However, The cracking catalyst also contains high concentrations of light REEs such as Ce, Pr, Nd (Kitto et al, 1992;Kulkarni et al, 2007). Therefore, if the cracking catalyst was the source, the excesses of light REEs would be expected along with La and Gd excesses.…”
Section: Source Of La and Gd (And Possibly Y) Excessesmentioning
confidence: 99%
“…Among these rare metals, rare earth elements (REEs) have been noticed (Sholkovitz et al, 1993;Bau and Dulski, 1996;Nozaki et al, 2000;Wang et al, 2001;Rühling and Tyler, 2004;Aubert et al, 2006;Kulkarni et al, 2006;Shimamura et al, 2007;Ryu et al, 2007). Shale-normalized (or upper crust average-normalized) REE patterns in precipitation, particle matters in precipitation, or aerosols were usually different from those in the upper crust or in sea water (Kitto et al, 1992;Sholkovitz et al, 1993;Zhang and Liu, 2004;Kulkarni et al, 2006;Moreno et al, 2008). It is difficult to explain these REE patterns by the simple mixing of oceanic and crustal sources (Zhang and Liu, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial to monitor REEs in PM 2.5 , especially in industrial environments, because they are the sole tracers to track fluidized-bed catalytic cracking (FCC) emissions from petroleum refining operations [10,11,13]. Even though La and Ce have been reported for vehicle PM 2.5 emissions [14,15] and occasionally in ambient PM [4,9], analyzing other lanthanides is essential to identify loss of FCC catalysts from petroleum refineries and their contributions to ambient PM 2.5 .…”
Section: Introductionmentioning
confidence: 99%